2021
DOI: 10.1097/mjt.0000000000001388
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Genetic Polymorphism of the CYP2D6 Gene on the Efficacy and Safety of Fluvoxamine in Major Depressive Disorder

Abstract: Background: Previous studies have shown that cytochrome P450 2D6 (CYP2D6) is involved in the metabolism of fluvoxamine, the activity of which is highly dependent, inter alia, on the polymorphism of the gene encoding it. The objective of our study was to investigate the effect of 1846G.A polymorphism of the CYP2D6 gene on the efficacy and safety of fluvoxamine, using findings on CYP2D6 enzymatic activity and on CYP2D6 expression level in patients with depressive disorders comorbid with alcohol use disorder.Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Studies in adult patients showed conflicting results, too [ 24 , 25 , 26 , 27 , 28 ]. The result of nonlinearity in smaller studies might be modulated by CYP2D6 gene variants, which were not considered in any study and can remarkably affect plasma exposure to fluvoxamine [ 29 , 30 , 31 , 32 ]. Unfortunately, no data on metabolizer status were available in the present sample.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in adult patients showed conflicting results, too [ 24 , 25 , 26 , 27 , 28 ]. The result of nonlinearity in smaller studies might be modulated by CYP2D6 gene variants, which were not considered in any study and can remarkably affect plasma exposure to fluvoxamine [ 29 , 30 , 31 , 32 ]. Unfortunately, no data on metabolizer status were available in the present sample.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies have shown as well that SSRIs improved both depressive symptoms and craving measures [ 19 ] and confirmed the efficacy of fluoxetine, fluvoxamine, and citalopram in treating depression in MDD + AUD patients, with statistically significant differences related to the presence of CYP polymorphisms [ 20 - 22 ]. However, these findings were limited by the small sample size, the heterogeneity of inclusion criteria, and the lack of a control group.…”
Section: Introductionmentioning
confidence: 92%
“…Drug efficacy stratification may be the result of individual differences in blood concentrations which caused by genetic polymorphisms of metabolic enzymes and drug interactions. Cytochrome P450 family member 2D6 (CYP2D6) is a major enzyme involved in catalyzing metabolism of fluvoxamine, which produced desmethyl fluvoxamine (Hicks et al, 2015;Zastrozhin et al, 2021). However, there are genetic polymorphism of CYP2D6 resulting in large inter-individual variability in enzyme activity, further leading to subtherapeutic phenomena or severe adverse effects (Zastrozhin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Cytochrome P450 family member 2D6 (CYP2D6) is a major enzyme involved in catalyzing metabolism of fluvoxamine, which produced desmethyl fluvoxamine (Hicks et al, 2015;Zastrozhin et al, 2021). However, there are genetic polymorphism of CYP2D6 resulting in large inter-individual variability in enzyme activity, further leading to subtherapeutic phenomena or severe adverse effects (Zastrozhin et al, 2021). Moreover, interactions between fluvoxamine and other drugs are frequently being reported.…”
Section: Introductionmentioning
confidence: 99%